ANALYSIS OF THE STAGES OF FORMATION OF THE UZBEK PEOPLE (Conferencea, 2025)
The final stage in the formation of the Uzbek people is characterized by the consolidation of the ethnic group and the emergence of modern Uzbek national identity. This process was influenced by historical, social, and political factors, including the formation of a unified state, the development of the Uzbek language, and the integration of various cultural elements. This article explores the key stages of the Uzbek people's formation, with a focus on the factors that led to the creation of a distinct Uzbek identity. The period of the khanates plays a crucial role in the development of Uzbek ethnic and cultural foundations.